1999
DOI: 10.1046/j.1365-2613.1999.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing myoepithelial cell distribution during regeneration of rat parotid glands.

Abstract: The distribution of the myoepithelial cells during regeneration of the rat parotid gland after atrophy induced by one week of parotid duct ligation was investigated by immunohistochemistry for actin and transmission electron microscopy (TEM). Immunohistochemically, residual ducts were surrounded by actin-positive cells when clips were removed from the duct. Three days later, most of the newly formed acini originating from the residual ducts were also embraced by actin-positive cells. After 10 days, actin-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
(67 reference statements)
1
8
0
2
Order By: Relevance
“…Previous studies have shown that surgical treatments induce cell proliferation in the salivary gland [15, 40, 41]. The present results, therefore, suggest that surgical resection and incision of the unilateral submandibular gland induce proliferation of MECs in residual and NC glandular tissues.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previous studies have shown that surgical treatments induce cell proliferation in the salivary gland [15, 40, 41]. The present results, therefore, suggest that surgical resection and incision of the unilateral submandibular gland induce proliferation of MECs in residual and NC glandular tissues.…”
Section: Discussionsupporting
confidence: 73%
“…Compensatory hypertrophy has been reported in the liver following partial resection, and in the lung after unilateral excision [48]. The quantitative compensation of secretory function by proliferation of acinar cells and MECs during regeneration has also been reported [15, 40, 41]. Our recent study showed that salivary gland resection induced acinar cell differentiation from the intercalated duct in the residual tissue of the operated side, as well as the NC side in adult rats [25].…”
Section: Introductionmentioning
confidence: 95%
“…The second hypothesis involves migration of myoepithelial cells. It has been suggested that myoepithelial cells migrate from acini to intercalated ducts during regeneration of rat parotid glands (16). In atrophic sublingual glands, myoepithelial cells may shift from small to large ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Myoepithelial cells are generally located around acini and intercalated ducts in salivary glands (6, 13, 14); however, it has been reported that there are myoepithelial cells at the periphery of striated and interlobular excretory ducts in human salivary glands (15) and that the myoepithelial cell distribution changes during development (6, 9) and regeneration (16) of rat parotid glands.…”
mentioning
confidence: 99%
“…Die Ursprungszellen für die Regeneration von Azinuszellen nach deren vollständiger Ablation sind Zellen der Gangepithelien [142]. Während dieser Regeneration nehmen myoepitheliale Zellen Kontakt zu den sich neu bildenden Azini auf [141]. Über die molekularen Signale, die sich zwischen diesen Zellen während der Regeneration abspielen, ist derzeit nichts bekannt.…”
Section: S 10unclassified